Heilige, Heiliges und Heiligkeit in spätantiken Religionskulturen - Gemeinhardt, Peter; Heyden, Katharina (Religionsgeschichtliche Versuche und Vorarbeiten, 2012)
The meaning of holiness and how one can speak about it remains an active research question in religious studies and theology. The articles analyze discourses about holiness from the religious cultures of late antiquity. Terminologies, practices, and reflections related to holiness are explored in the context of their particular religious frames of reference